ANALISIS GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PERANGKAT DESA DI KECAMATAN CERMEE KABUPATEN BONDOWOSO DENGAN DISIPLIN KERJA - Zainullah, Muhammad; Karnadi, Karnadi; Tulhusnah, Lusiana (Fakultas Ekonomi dan Bisnis, 2023)
A village office is a building or room that is used as a village-level government administration center. The village office functions as a gathering place for village government officials, including the village head, village administration staff, as well as various sections or units related to public services and the interests of village communities. This research aims to investigate the influence of leadership style and work motivation on the performance of village officials in Cermee District, Bondowoso Regency. The aims of this research is to find out whether work discipline mediates the relationship between leadership style and work motivation and the performance of village officials. The population in this research is the Banyuputih District Village apparatus. The sampling technique uses saturated sampling. Data analysis and hypothesis testing in this research used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application show that . Leadership style has a significant effect on work discipline, work motivation has a significant effect on work discipline, leadership style has a significant effect on performance, work motivation has an insignificant effect on performance, work discipline has an insignificant effect on performance. The results of the indirect influence hypothesis test show that the leadership style variable has no significant effect on performance through work discipline, work motivation has no significant effect on performance through work discipline.